Analysis of Internal Control in The Process of Granting at Public Administration Bureau Regional Secretariat of East Java Province - Nurul Lathifah (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study was to analyze and evaluate the internal control of the process of granting at the East Java Provincial Secretariat's Public Administration Bureau. This research is a qualitative research with an explanatory approach to explore the causes of internal control problems in depth and evaluate them, ask questions, and answer problems so as to find solutions and provide appropriate recommendations. The subject of this research is the Public Administration Bureau of the Regional Secretariat of East Java Province. The object of this research is internal control in the process of granting. Data analysis begins with making preliminary observations regarding the process of budgeting, disbursing, and reporting grant funds as well as an internal control system then organizing and preparing data for analysis by verifying and evaluating data from interviews, observations, and documentation, and comparing the data obtained with theory and make conclusions and suggestions. The results of this study indicate that the Public Administration Bureau of the Regional Secretariat of East Java Province has implemented five components of COSO internal control, namely the control environment, risk assessment, control activities, information and communication, and monitoring activities with 17 control principles in the process of granting and implementing them based on Government Regulation No. 60 of 2008. The internal control system of the Public Administration Bureau of the Regional Secretariat of East Java Province in the process of providing grant funds is in accordance with the theory of internal control according to COSO and Government Regulation No. 60 of 2008. But in practice, there are still obstacles, namely limited human resources (employees), human error, differences in the educational levels of grant recipients, and changes in policies and regulations.